3 D Porous Nickel–Cobalt Nitrides Supported on Nickel Foam as Efficient Electrocatalysts for Overall Water Splitting. Issue 21 (12th October 2017) - Wang, Yueqing; Zhang, Baohua; Pan, Wei; Ma, Houyi; Zhang, Jintao
Abstract: Exploring highly efficient and durable bifunctional electrocatalysts from earth‐abundant low‐cost transition metals is central to obtaining clean hydrogen energy through large‐scale electrolytic water splitting. Porous nickel–cobalt nitride nanosheets on macroporous Ni foam (NF) are synthesized through facile electrodeposition followed by a one‐step annealing process in a NH3 atmosphere. The transformation from a metal hydroxide into a metal nitride could efficiently enhance the electrocatalytic performance for both the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). Interestingly, the incorporation of nickel further boosts the catalytic activity of cobalt nitride. When used as bifunctional electrocatalysts, the obtained nickel–cobalt nitride electrocatalyst shows good stability and superior catalytic performance toward both HER and OER with low overpotentials of 0.29 and 0.18 V, respectively, to achieve a current density of 10 mA cm −2 . The good electrocatalytic performance was also evidenced by the fabrication of an electrolyzer for overall water splitting, which exhibits a high gas generation rate for hydrogen and oxygen with excellent stability during prolonged alkaline water electrolysis. The present work provides an efficient approach to prepare a 3 D interconnected porous nickel–cobalt nitride network with exposed inner active sites for overall water splitting. Abstract : 3 D porous bimetallic nickel–cobalt nitrides are grown on nickel foam as electrocatalysts with excellent catalytic activity for water splitting in an alkaline electrolyte. The nitridation treatment is an efficient approach to promote the catalytic performance, and the incorporation of nickel further boosts the catalytic activity.